Kidney clear cell sarcoma: About one case - Allouche, Fadwa; Mazti, Asmae; Terrab, Fatima Zahra; Ghammad, Sanae; Bouhafa, Touria; El Mazghi, Abderrahmane; Hassouni, Khalid (Journal of Surgery and Medicine, 2018)
Kidney Clear Cell Sarcoma (SRCC) is a rare malignant tumor of the child, recognized for its aggressiveness, its high bone metastatic potential and its tendency to recur. We report a case diagnosed SRCC in a 22-month-old infant with a large right lumbar mass. An observation of Kidney tumor type clear-cell sarcoma, whose diagnosis was placed on a piece of anatomo-pathology, insofar as the imaging remained uncertain as to the Kidney origin of this mass. Apart from the histological aspect, there is currently no criterion for its diagnosis. Its prognosis has been markedly improved by the introduction of new treatment regimens.